How Have Post-9/11 Wars Been Gendered? - Sarac, Busra Nisa (2016)
The study evaluated the gendered representation of ‘War on Terror’ in the wars in Iraq and Afghanistan. In order to do that, the study looked at the participation of women in the UK and US armed forces as a case study. Women’s violence was examined as opposed to their established gendered roles with instances of female icons participating in these wars in Iraq and Afghanistan. The study includes historical background of role of women in war, how to understand manhood in relation to war, the social construction of women in relation to war, feminist perspectives (colonial feminism and pacifist feminism) towards the wars, and the transformation of women from Home-Front to Front-Line after the 9/11. To understand representation of women and collect data, the reports by UK Ministry of Defense(MoD), UK Parliament records, and reports by the US Department of Defense were used.In particular, the sources published after the 9/11 have been analysed in an effort to provide better analysis of notion of women in relation to the wars. It means that the study incorporates the years between 2001 and 2014. The study figured out that the rhetoric of women’s rights was used as a justification to wage the wars in Iraq and Afghanistan. The sources were selected through their discussions about the place of women in relation to that of men in the wars. That is another analysis of the research that the representations and roles of women were defined to consolidate the notion of hegemonic masculinity. In a nutshell, this study has examined the relation between gender and war in an effort to understand how the wars after the 9/11 have changed gendered roles.